Hubungan Riwayat Imunisasi Dasar dan Penyakit Infeksi dengan Kejadian Stunting di Puskesmas Cot Seumeureung, Kabupaten Aceh Barat - Yulia, Maurina Firmi; Rinawati, Rinawati; Putri, Suci Eka; Putri, Enda Silvia (Medan Resource Center, 2024)
Stunting is a medical condition characterized by height significantly below the standard -2 SD z-score, adversely affecting children's physical growth and cognitive development. This study aims to analyze the correlation between basic immunization records, infectious disease history, and stunting prevalence in Cot Seumeureung Puskesmas, Aceh Barat. A quantitative cross-sectional method was employed, utilizing Chi-Square analysis (p-value < 0.05 indicating significance). Findings revealed a significant association between lack of immunization and previous infections, such as diarrhea (p=0.004, RP=1.63), with the incidence of stunting. These results underscore the crucial role of immunization and regular health monitoring as preventive measures. Furthermore, the study highlights the need for strengthened public health strategies to reduce stunting rates, emphasizing comprehensive immunization coverage and early intervention for infectious diseases. Future research could explore additional factors, including maternal nutrition and environmental conditions, contributing to stunting.